Answer:
C
Step-by-step explanation:
Answer:
x>9
Step-by-step explanation:
When x is -1 Y will equal -1
Let's call the two numbers a and b. So we know that the difference of the two numbers is 36:
a - b = 36
And we know that their sum is 286:
a + b = 286
We can use either of these equations to solve for one of the variables in terms of the other variable. Let's use the first and solve for a:
a - b = 36
a = 36 + b
Now we plug this into the other equation and solve for b there:
(36 + b) + b = 286
36 + 2b = 286
2b = 250
b = 125